MOESM4 of Differential expression of the aryl hydrocarbon receptor pathway associates with craniofacial polymorphism in sympatric Arctic charr - Ahi, Ehsan; Steinhäuser, Sophie; Pálsson, Arnar; Sigrídur Franzdóttir; Sigurdur Snorrason; Maier, Valerie; Jónsson, Zophonías (Figshare, 2015)
Additional file 4: Table S4. Transcription factor enrichment analysis using WEB-based GEne SeT AnaLysis Toolkit (WebGestalt v2). The list of more than 200 genes co-expressed with Chd4, Cspp1 and Dlg1 in human and mice are used as input. (Cut-off criteria: p